In vitro and in vivo metabolism of psilocybin’s active metabolite psilocin - Thomann, Jan; Kolaczynska, Karolina E.; Stoeckmann, Oliver V.; Rudin, Deborah; Vizeli, Patrick; Hoener, Marius C.; Pryce, Christopher R.; Vollenweider, Franz X.; Liechti, Matthias E.; Duthaler, Urs (Frontiers in Pharmacology, 2024)
In vivo, psilocybin is rapidly dephosphorylated to psilocin which induces psychedelic effects by interacting with the 5-HT2A receptor. Psilocin primarily undergoes glucuronidation or conversion to 4-hydroxyindole-3-acetic acid (4-HIAA). Herein, we investigated psilocybin’s metabolic pathways in vitro and in vivo, conducting a thorough analysis of the enzymes involved. Metabolism studies were performed using human liver microsomes (HLM), cytochrome P450 (CYP) enzymes, monoamine oxidases (MAO), and UDP-glucuronosyltransferases (UGT). In vivo, metabolism was examined using male C57BL/6J mice and human plasma samples. Approximately 29% of psilocin was metabolized by HLM, while recombinant CYP2D6 and CYP3A4 metabolized nearly 100% and 40% of psilocin, respectively. Notably, 4-HIAA and 4-hydroxytryptophol (4-HTP) were detected with HLM but not with recombinant CYPs. MAO-A transformed psilocin into minimal amounts of 4-HIAA and 4-HTP. 4-HTP was only present in vitro. Neither 4-HIAA nor 4-HTP showed relevant interactions at assessed 5-HT receptors. In contrast to in vivo data, UGT1A10 did not extensively metabolize psilocin in vitro. Furthermore, two putative metabolites were observed. N-methyl-4-hydroxytryptamine (norpsilocin) was identified in vitro (CYP2D6) and in mice, while an oxidized metabolite was detected in vitro (CYP2D6) and in humans. However, the CYP2D6 genotype did not influence psilocin plasma concentrations in humans. In conclusion, MAO-A, CYP2D6, and CYP3A4 are involved in psilocin’s metabolism. The discovery of putative norpsilocin in mice and oxidized psilocin in humans further unravels psilocin's metabolism. Despite limitations in replicating phase II metabolism in vitro, these findings hold significance for studying drug-drug interactions and advancing research on psilocybin as a therapeutic agent.